Changes in Chronotype after Stroke: A Pilot Study - Kantermann, Thomas; Meisel, Andreas; Fitzthum, Katharina; Penzel, Thomas; Fietze, Ingo; Ulm, Lena (Frontiers in Neurology, 2015)
This study aimed to elucidate associations between stroke onset and severity as well as chronotype (phase of entrainment) and internal time of stroke. Fifty-six first-ever ischemic stroke patients participated in a cross-sectional study assessing chronotype (mid-sleep on work-free days corrected for sleep deficit on workdays; MSFsc) by applying the Munich ChronoType Questionnaire (MCTQ). The MCTQ was completed twice, on average 68 ± 24 (SD) days post stroke and retrospectively for the time before stroke. To assess the impact of stroke in relation to internal time, InTstroke was calculated as MSFsc minus local time of stroke. Stroke severity was assessed via the standard clinical National Institute Health Stroke Scale (NIHSS) and modified Ranking Scale (mRS), both at hospital admission and discharge. Overall, most strokes occurred between noon and midnight. There was no significant association between MSFsc and stroke onset. MSFsc changed significantly after stroke, especially in patients with more severe strokes. Changes in MSFsc varied with InTstroke – the earlier the internal time of a stroke relative to MSFsc-before-stroke, the more MSFsc advanced after stroke. In addition, we provide first evidence that MSFsc changes varied between stroke locations. Larger trials are needed to confirm these findings.